Biogas enhancement with membranes - McLeod, Andrew J. (Cranfield University, 2014)
Biogas is generated during anaerobic digestion (AD) of sewage sludge at wastewater treatment works (WWTW) and consists of approximately 50-70 % methane (CH4) balanced primarily by carbon dioxide (CO2). It is commonly used directly as a fuel gas for the renewable generation of electricity on-site by combined heat and power (CHP) engines. However, as a result of governmental incentivisation, biogas possesses a greater value when applied to the national gas grid as a natural gas substitute. However, this requires enhancement of the CH4 content to that comparable to natural gas by selective removal of CO2; a process known as biogas upgrading. This thesis explores the potential of hydrophobic micro-porous hollow fibre membrane contactors (HFMCs) to biogas upgrading. HFMCs allow non-dispersive contact between the biogas and a liquid solvent for the preferential absorption of CO2, which is conventionally facilitated by packed-column gas scrubbing technology. However, recent gas absorption literature has demonstrated many practical and operational advantages of HFMCs, which suggests they may be effective for biogas upgrading at WWTW. In this thesis, HFMCs were used to explore the mechanism and controllability of the undesirable co-absorption of CH4, known as methane slip. This was found to be attributable to the phase limiting mass transfer, with liquid-limited physical absorption in water exhibited 5.2 % slip whereas gas-limited chemical absorption displayed just 0.1 %. Ammonia-rich wastewaters were investigated as sustainable chemical absorbents using HFMCs and exhibited comparable chemically enhanced absorption to analogue synthetic ammonia solutions. The recovery of the subsequent reaction product (ammonium bicarbonate) by crystallisation facilitated by the membrane was also examined. The potential of this approach was summarised within two hypothetical wastewater flowsheets, where upgrading using a return liquor absorbent acts as a return liquor treatment and where ion exchange allows 100 % application of wastewater derived ammonia to biogas upgrading. These both offered potential economic advantages versus conventional flowsheets with 100 % biogas application to CHP.